In search of a monetary constitution - Yeager, Leland B. (Cambridge : Harvard University Press, 1962)
This book is an outgrowth of eleven lectures delivered at the Thomas Jefferson Center for Studies in Political Economy of the University of Virginia in the fall of 1960. It examines a line of thinking on monetary reform in which decentralized organization of economic life by means of markets, money, and prices is an indispensable to human freedom.
"An outgrowth of eleven lectures delivered at the Thomas Jefferson Center for Studies in Political Economy of the University of Virginia in the fall of 1960."
Includes index
Bibliographical footnotes.
usc 26/07/2017
Loans
Keywords: Monetary policy; United States